ANALISA KEAMANAN SISTEM INFORMASI MENGGUNAKAN FRAMEWORK COBIT 5 DENGAN DOMAIN DSS05 DAN APO13 DI PT XYZ - Yeremia Tomi Sepis (Fakultas Teknologi Informasi - Universitas Advent Indonesia, 2022)
The PT XYZ is one of the educational institutions that often uses information technology to support operational activities to be more effective and efficient. This study aims to determine how the security of information systems at the PT XYZ has a security level that is at a certain level of measurement standards is to use the Cobit 5 framework DSS05 and APO13 domains. Respondents to get the data security system is the head of the IT department at PT XYZ. Process To get the results of the interviews that have been conducted, researchers use the formulas that are already in the COBIT 5 book. The results obtained from the DSS05 Domain indicate that the security of the system at PT XYZ is at level 2 which means that the security of the system has been running based on planning, monitoring, and adjustments but in the APO13 Domain shows that the security of the system has not been implemented or has not been implemented because of the level obtained at level 0. Therefore it is necessary to improve the existing security system at PT XYZ according to the COBIT 5 Framework standard.